Bibliometric analysis of Nobelists' awards and landmark papers in physiology or medicine during 1983–2012. (December 2013) - Ye, Siqi; Xing, Rui; Liu, Jing; Xing, Feiyue
Abstract Aim. This study's purpose was to determine if there was a relationship between Nobel Laureates' awards and landmark papers and winning the Nobel Prize in Physiology or Medicine during 1983–2012. Methods. The 66 Nobelists' awards and landmark papers in the period 1983–2012 were analyzed. Results. The results showed that the most Nobelists had won Gairdner, Lasker, Howitz or Wolf Award before they won Nobel Prize, indicating that Gairdner Award may be considered as a Nobel Prize's wind vane. A small number of landmark papers were indeed published in low impact factor journals (10.5% below impact factor 5.0) and some of their citation were low (23.2% below 400 times). There were 61 of 76 landmark papers published in the journals of JCR partition 1, reaching 80%, but 2 of 76 landmark papers were even outside of JCR partition, demonstrating that JCR partition acts as a reciprocal supplement with impact factor and citation times. The test period of Nobel Prize was substantially between 10 to 30 years. There were 5 persons whose landmark papers were cited all above 6000 times to get Nobel Prize within the test period of ten years, suggesting that there is a trend of certain inverse ratio between the citation and the test period of Nobel Prize. Conclusion. These findings provide a new insight into the relationship among Nobel Laureates' awards, landmark papers and Nobel Prize in Physiology or Medicine.